The Importance of Understanding Students’ Characteristics in The Learning Process of Kurikulum Merdeka - Khomsah, Fitriani; WL, Maria Yosephin; Shopia B, Theresia Cicik; Widyastuti, Ely Wahyu (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
This research explained the importance of understanding students’ characteristics in the learning process of Kurikulum Merdeka. This research is descriptive qualitative research that involves class XI Clothing 3 as the subject of the research. The instrument of this research used questionnaires distributed to students who were taught during PPL 1 at SMK N 6 Semarang. The result of this research is that understanding the characters of students greatly determines the learning outcomes to be achieved, activities that need to be carried out, and appropriate assessments for students. In relation to the implementation of the learning process in the Kurikulum Merdeka, teachers have the freedom to choose, modify, or compile their own teaching modules that have been provided by the government to adapt the teaching modules to the characteristics of students.